PERAN SISTEM INFORMASI DALAM REKRUTMEN RELAWAN PASKAS DI MASJID KAPAL MUNZALAN PONTIANAK - MASPUPAH Maspupah; Fakhrurosi Fakhrurosi; Raziki Waldan (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
The increasing reliance on digital technologies has reshaped human resource practices across various sectors, yet studies on how digital information systems support volunteer recruitment within faith-based and community organizations remain limited. Traditional recruitment methods often face challenges related to administrative inefficiency, limited outreach, and inadequate data validation. This study aims to analyze the role of digital information systems in improving the effectiveness, efficiency, and accountability of volunteer recruitment processes within a community-based religious organization. A descriptive qualitative case study was employed, involving in-depth interviews with recruitment administrators, senior volunteers, and newly registered volunteers. Additional data were collected through digital documentation, online registration forms, social media content, and non-participant observation. Thematic analysis was used to identify patterns relating to recruitment stages, system integration, and user responses. The findings reveal that digital information systems particularly social media platforms, messaging applications, and online registration forms significantly streamline the recruitment process. These tools accelerate information dissemination, simplify administrative screening, and enhance data validation through combined digital and offline verification. The system also increases the accessibility of recruitment channels and contributes to a higher number and better quality of volunteer applicants. Minor challenges such as input errors and communication gaps were present but easily resolved due to the digital literacy of most users. This study demonstrates that integrating digital information systems into volunteer recruitment enhances operational efficiency, strengthens communication, and improves the overall quality of human resource management in community-based organizations. The findings can serve as a model for religious, social, and non-profit institutions seeking to digitize their recruitment workflows. The study offers a new perspective by examining the digital transformation of volunteer recruitment within a religious community setting an area rarely explored in prior research. It highlights a hybrid model of recruitment that combines online administration with offline validation, ensuring both efficiency and authenticity in volunteer selection.